A Comparative Analysis of Local Maize Hybrids, Versus Commercial Maize Hybrids: Assessing Yield and Yield Components - Saleem, Muhammad Ahmad; Anwar, Shazma; Khan, Muhammad Yasir; Saleem, Abdul Samad; Khan, Muhammad Shahzad; Shafi Ur Rahman; Khattak, Laiba; Khan, Amjad; Murad, Shayan; Noor, Emaan; Khan, Kashif Ahmad (International Journal of Sustainability in Research, 2024)
Genetic variability is an important factor for genotype selection in order to increase yield. A field experiment was conducted on “A comparative analysis of local maize hybrids, versus commercial maize hybrids: Assessing yield and yield components” was carried out at Cereal Crops Research Institute (CCRI) Pirsabak Nowshera during 2022, to check the performance of forty maize hybrids i.e., CHTW-1 to CHTW-40 along 2 checks (CS-220 and P30K08). Randomized complete block design (RCBD) was used with 3 replications. Two rows of each hybrid, each measuring five meters, were planted. The row-to-row and plant-to-plant distance maintained was 75 cm and 25 cm respectively. The seed rate used was 25 kg ha-1.  Statistical analysis of the data showed that maximum days to tasseling (60.67 days) were taken by check hybrid CS-220 while minimum days to tasseling (50 days) was noted in candidate hybrids CHTW-2 and CHTW-20. From the results it is concluded and recommended that the candidate hybrid CHTW-11 should be purchased and sown by the farmers as this is the finest, high yielding and cheaper as compared to other maize hybrids available in the market.